2000
DOI: 10.3923/pjbs.2000.292.295
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Seed Size on Germination, Emergence, Growth and Seedling Survival of Senna occidentalis Link.

Abstract: Seed size variation and its effects on germination and seedling growth were examined in seeds collected from a population of Senna occidantalis. Seed size varied from 0.009-0.029 g per seed. Final germination percentage depended on seed size with large seeds having highest germination percentage, but germination velocity was higher for small seeds. Seedlings from large seeds produced longer roots and shoots than those from small seeds and were able to emerge more rapidly. The seed size had a clear effect on su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 31 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…This interference may be particularly important in plants with a higher degree of pollinator specialization, such as some Ferocactus species, whose flowers are pollinated almost exclusively by cactus-specialist bees like Diadasia rinconis (McIntosh, 2005). Our study found that the reduction in the number and size of seeds produced by flowers visited by ants may be associated with a lower rate of bee visits, resulting in less pollen deposition on flower stigmas and ultimately reducing the number of seeds produced, as well as their size and weight, traits associated with seed germination and survival (Saeed & Shaukat, 2017).…”
Section: Impact On Plant Pollination and Fitnessmentioning
confidence: 60%
“…This interference may be particularly important in plants with a higher degree of pollinator specialization, such as some Ferocactus species, whose flowers are pollinated almost exclusively by cactus-specialist bees like Diadasia rinconis (McIntosh, 2005). Our study found that the reduction in the number and size of seeds produced by flowers visited by ants may be associated with a lower rate of bee visits, resulting in less pollen deposition on flower stigmas and ultimately reducing the number of seeds produced, as well as their size and weight, traits associated with seed germination and survival (Saeed & Shaukat, 2017).…”
Section: Impact On Plant Pollination and Fitnessmentioning
confidence: 60%
“…McKersie, et al [27], noted that larger seed sizes of bird's-foot trefoil improved field establishment. Similarly, Saeed and Shaukat [28] observed that large Senna occidentalis seeds had a higher germination rate, longer seedling roots and shoots than small seeds. Mao, et al [29], noted that large seed had higher 1000-seed weight and soluble sugar concentration and exhibited higher germination index, vigor index, and seedling biomass than small seeds.…”
Section: Resultsmentioning
confidence: 81%
“…However, Siddig et al (2015) reported the increase growth parameters of faba bean like seedling length, number of leaves per plant, with an increase in seed size of faba bean. Other contradictory idea is also reported from Senna occidentalis Link by Saeed and Shaukat (2000). The found that small seed category showed lesser seedling growth while large seeds showed greater seedling growth i.e., root and shoot growth of seedlings was greater in case of large seeds.…”
Section: Effect Of Seed Size and Sowing Depth On Faba Bean Growthmentioning
confidence: 90%
“…They reported that small and large seeds had significantly the highest and least germination rates respectively. However, a contradictory result was reported Saeed and Shaukat (2000) for seed size and germination in Senna occidentalis Link. The researchers reported that seed size/weight in Senna occidentals exhibited a significant effect on seed germination and emergence percentage with large seeds showing greater germination as well as emergence percentages.…”
Section: Effect Of Seed Size and Sowing Depth On Faba Bean Germinationmentioning
confidence: 93%